2 answers:
Answer:
x = 6
y = -6
Step-by-step explanation:
By adding both equations :-
=》-4x -2y + 4x + 8y = -12 + (-24)
=》-4x + 4x + 8y - 2y = -12 - 24
=》6y = -36
=》y = -36 ÷ 6
=》y = -6
putting the value of y in equation 2
=》4x + 8y = -24
=》4x + (8 × -6) = -24
=》4x - 48= -24
=》4x = 48 - 24
=》x = 24 / 4
=》x = 6
Add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.
Answer:
X=6, Y=-6
You might be interested in
-10x + 20 should be the right answer.
Answer:
6
Step-by-step explanation:
the hypotenuse should be 3√2*√2=6
Answer:
6
Step-by-step explanation:
tan 45 = 6 / x
1 = 6 / x
x = 6
Note :
Tan 45 value = 1
It would have changed by 1/3 is ur answer
Answer:
-2
Step-by-step explanation: